Recent advances in economics : a book of readings - Fels, Rendigs; Siegfried, John J.; American Economic Association (Homewood, Ill. : Published for the American Economic Association by R. D. Irwin, 1974)
The book is aimed at helping economics teachers with heavy teaching loads to keep up with their field. The book will also be useful for undergraduate majors in economics and graduate students in the social sciences.
Includes bibliographies.
rpm 14/09/2017
Loans
Keywords: Economics